Plantations enabling mines: Incremental industrial extraction, social differentiation and livelihood change in East Kalimantan, Indonesia. (August 2022) - Toumbourou, Tessa D.; Dressler, Wolfram H.; Werner, Tim T.
Abstract: How do uneven agrarian histories and resource sectors intersect to yield new extractive developments in one landscape? How are local livelihoods, social relations and differentiation implicated in cumulative extractivism over time? Contributing to emerging literature on the political ecology of cross-sectoral extractive development, we answer these questions by examining the origins and interactions of overlapping phases of resource extraction and the uneven livelihood implications for different social groups in frontier Southeast Asia. Drawing on a case in East Kalimantan, Indonesia, we show how seemingly separate processes of extractivism––industrial logging, palm oil plantations and coal mining–– overlap and reinforce one another to enhance uneven access to and use of land and forest resources, social differentiation and NGO-enabled resistance in a Dayak Modang community. While older Modang involved in early land clearing dynamics had secured greater landholdings and were bettered positioned to diversify livelihoods, younger Modang and migrants experienced greater livelihood constraints and precarity in the overlapping spaces claimed by palm oil and now coal mining. As land availability declined with the expansion of plantations and mines, locally perceived differences ran along ethnic lines and adat (customary) markers leveraged by NGOs, reinforcing tensions among 'indigenous' and 'migrant' peoples. We argue that as social differentiation sharpens, 'collective' resistance against expanding plantations and mines became becomes increasingly difficult. Our paper suggests that paying attention to how and why historical processes of extractivism and land accumulation work synergistically can provide deeper insights into how social differentiation and livelihood insecurity unfolds in terms of the spatial and temporal character of landscapes. Highlights: Past phases of resource extraction overlap and reinforce one another, enhancing uneven access to and use of land and livelihood resources for different social groups in Kalimantan, Indonesia. Narrowing access to land and livelihood opportunities affects younger generations of Dayak and newly arrived migrants most detrimentally. Underlying livelihood challenges and a lack of access to land compels local people to enrol in further phases of resource extraction.